Enhancing adsorption efficiency of methylene blue from water using cassava rhizome-derived mesoporous activated carbons prepared via one-pot hydrothermal carbonization - Phuriragpitikhon, Jenjira; Pluamjai, Kittiya; Fuangchoonuch, Warinda; Chuenchom, Laemthong (Bulletin of Applied Sciences, 2022)
The textile dyeing industry is one of the important midstream industries for textile industry in Thailand. This production process requires dyes as the main components. When such contaminated wastewater is discharged into public water, this negatively affects surrounding ecosystems and human health. The present work aims to improve the adsorption efficiency of agricultural residues derived activated carbons in removing dyes from textile dyeing effluent by the creation of the mesopores into the carbon structure. The activated carbons were prepared from cassava rhizome using ZnCl2 as an activating agent and were fabricated by one-pot hydrothermal carbonization, followed by the carbonization of the obtained hydrochars at 800 °C. The result demonstrated that the optimal condition to obtain activated carbons with a high specific surface area and the largest mesopore volume was using the mass ratio of ZnCl2 to cassava rhizome of 3 (3.0Z-AC). 3.0Z-AC possessed bimodal pore size distribution in the range of the micro and mesopores and had the specific surface area, the micropore- and mesopore volumes of 1,405 m2/g, 0.42 cm3/g and 0.54 cm3/g, respectively. Such a mesoporous activated carbon was used as the adsorbent to investigate the adsorption efficiency of methylene blue in dye-contaminated water. The adsorption behavior of methylene blue on 3.0Z-AC was monolayer adsorption based on the Langmuir isotherm model (R2 = 0.9993). The equilibrium time of 210 minutes and adsorption capacity of 274 mg/g were found for this sample, while the equilibrium time of the commercial activated carbon is 270 minutes and its maximum adsorption capacity is 260 mg/g.